Oxidative stress modulation in alcohol-related liver disease: From chinese botanical drugs to exercise-based interventions - Zhu, Yuting; Jia, Yuqing; Zhang, Enming (Frontiers in Pharmacology, 2025)
Alcohol-related liver disease (ALD) is a chronic liver injury caused by long-term excessive alcohol consumption, with complex and multifaceted pathological mechanisms. Research indicates that oxidative stress (OS), inflammatory responses, and lipid metabolic disturbances induced by alcohol and its metabolites are primary contributors to hepatocyte injury, positioning OS as a key target in ALD treatment. The main non-pharmacological treatment for ALD is alcohol abstinence, while medical treatment primarily relies on Western pharmacological interventions. However, recent research has increasingly highlighted the potential of Chinese botanical drugs in improving histological features and modulating signaling pathways associated with OS in ALD, underscoring the therapeutic potential of traditional Chinese herb medicine. Despite these promising findings, the precise mechanisms and effects of these extracts remain incompletely understood, and potential side effects must be considered. Therefore, a comprehensive analysis of herbal extracts with therapeutic effects is essential to optimize clinical administration and ensure safe, effective treatment. This review focuses on OS as a central theme, categorizing Chinese botanical drugs into six major groups—flavonoids, polyphenols, terpenoids, alkaloids, saponins, and anthraquinones—all widely used in traditional Chinese herb medicine. The review provides an overview of their botanical characteristics and therapeutic actions in the context of ALD, offering insights into OS regulation and exploring their potential as treatments for ALD. Notably, physical exercise shares overlapping mechanisms with botanical drugs in regulating OS. Combining two strategies could offer a promising integrative treatment for ALD, though further research is needed to confirm their synergistic benefits and optimize clinical applications.